Appearance and distribution of surface proteins of the human erythrocyte membrane. An electron microscope and immunochemical labeling study - Shotton, D. (The Rockefeller University Press, 1978)
We have used freeze-etching, before and after immunoferritin labeling, to visualize spectrin molecules and other surface proteins of the human erythrocyte membrane. After intramembrane particle aggregation was induced, spectrin molecules, identified by labeling with ferritin-conjugated antispectrin, were clustered on the cytoplasmic surface of the membrane in patches directly underlying the particle clusters. This labeling pattern confirms the involvement of spectrin in such particle aggregates, as previously inferred from indirect evidence. Ferritin-conjugated antihapten molecules, directed against external and cytoplasmic surface proteins of the erythrocyte membrane which had been covalently labeled nonspecifically with the hapten p-diazoniumphenyl-beta-D-lactoside, were similarly found in direct association with such intramembrane particle aggregates. This indicates that when spectrin and the intramembrane particles are aggregated, all the major proteins of the erythrocyte membrane are constrained to coaggregate with them. Although giving no direct information concerning the freedom of translational movement of proteins in the unperturbed erythrocyte membrane, these experiments suggest that a close dynamic association may exist between the integral and peripheral protein components of the membrane, such that immobilization of one component can restrict the lateral mobility of others.